Charge localization in 1D tetramerized organic conductors: the special case of (tTTF)2ClO4. (18th February 2019) - Frąckowiak, Arkadiusz; Świetlik, Roman; Jeannin, Olivier; Fourmigué, Marc; Li, Weiwu; Dressel, Martin
Abstract: We report a detailed structural and spectroscopic study of the 1D 2:1 cation radical salt (tTTF)2 ClO4, where tTTF = trimethylenetetrathiafulvalene, which exhibits a semiconductor-semiconductor phase transition at ca. T = 137 K. Crystal structures are determined above and below the transition; the tTTF molecules in stacks are grouped into weakly interacting tetramers. The reorganization of tTTF stacks is accompanied with an order-disorder transition in anion sublattice. Polarized infrared and Raman spectra of (tTTF)2 ClO4 are measured in the broad frequency range as a function of the temperature (10–293 K). The structural and vibrational features are investigated to elucidate the origin of the semiconductor-semiconductor phase transition. We discuss the electron-intramolecular vibration coupling effects in the vibrational spectra of (tTTF)2 ClO4 and identify signatures of high- and low-temperature states of charge localization in the tetramerized system. Both the C=C and C–S stretching modes of tTTF give evidence of strong charge distribution fluctuations in conducting stacks for T > 137 K, which are responsible for the appearance of molecules with charge +1 e, and charge localization in tTTF tetramers for T < 137 K. The uniqueness of the salt (tTTF)2 ClO4 in comparison with other tetramerized 1D systems is discussed.